IMPROVING STUDENTS’ VOCABULARY MASTERY ON NARRATIVE TEXT THROUGH MNEMONIC METHOD - Ndraha, Lies Dian M. (Universitas Nias Raya, 2022)
The research was designed in classroom action research (CAR). Observation paper of the researchers’ activities and students’ activities, and test were used as the instrument to collect the data needed. The research did action research in two cycles. Each cycle consisted of two meetings. The result of this action research was that the percentage of researchers done activities in meeting I of cycle I was 73 %, meanwhile in meeting II of cycle I was 83 %. Next, the percentage of students’ done activities in meeting I of cycle I was 69.9 %, meanwhile in meeting II of cycle I was 87.2 %. The average of students’ score in cycle I was 67.3. Furthemore, the percentage of researchers done activites in meeting I of cycle II was 93 %, meanwhile in meeting II in cycle II was 100 %. Next, the percentage of the students’ done activities in meeting I of cycle II 93.6 %, meanwhile in meeting II of cycle II was 94.8 %. The average students’ score in cycle II was 88.1. It was concluded that there was improvement of students’ vocabulary through Mnemonic method.